The Impact of Household Capital Income on Income Inequality - A Factor Decomposition Analysis for the UK, Germany and the USA - Anna Fräßdorf; Markus M. Grabka; Johannes Schwarze (The Journal of Economic Inequality, 2011)
This paper analyses the contribution of capital income to income inequality in a cross-national comparison. Using micro-data from the Cross-National Equivalent File (CNEF) for three prominent panel studies, namely the BHPS for the UK, the SOEP for West Germany, and the PSID for the USA, we use the factor decomposition method described by Shorrocks (Econometrica 50:193–211, 1982). The factor decomposition of disposable income into single income components shows that capital income is exceedingly volatile and that its share in disposable income has risen recent years. Moreover, capital income makes a disproportionately high contribution to overall inequality in relation to its share in disposable income. This applies to Germany and the USA in particular. Thus capital income accounts for a large part of disparity in all three countries.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s10888-009-9125-4
Keywords: 330; Capital income; CNEF; Factor decomposition; Inequality; Einkommensverteilung; Panel; Ökonometrisches Modell; Vergleich; Deutschland; USA; Großbritannien